Сочинения: в 3 томах : перевод с древнегреческого (Платон) - Платон (1983)
Источник записи: Москва: Мысль, 1968 Экземпляры: БС (20240902) / Инвентарный номер: ФЖД12814 / Сис.шифр: 87.3(0) / Авт.знак: П 37 / ГРНТИ: 02 / ББК: 87.3(0)321